Desenvolvimento de um aplicativo para controle acadêmico em dispositivos móveis - OLIVEIRA, Jeferson Matheus Gomes (2017)
The objective of this Project is the creation of app for academic control in mobiles. The application is intended for the main daily tasks of the teacher and student; the teacher can input grades, input attendances by classes or students, send messages and consult the areas of knowledge of the college subjects, also available in the main menu the option to call more efficiently for the last class given; the student can consult the notes, frequencies, read warnings and consult his area of knowledge concentration. The area of knowledge concentration is an innovative method for monitoring student development according the criteria established by the competent agency. It is demonstrate the functional and non-functional requirements of the app as well as the Usage diagrams, Deployment and Database necessary for understanding of the work. A Webservice was developed, used to communicate between the app and database server of the web system. The application presented is designed to be a simple and easy-to-understand tool. Among the tools used for the development of source codes, was consider the use of Android Studio and Eclipse; Windows and Ubuntu operating systems; Java, PHP, HTML, XML and Javascript programming languages; of the PostgreSQL and SQLite databases; of the Apache web application server. In the final step are presented the screens of the app separated by the views of the teacher and student, as well as their explanation.